2020
DOI: 10.30577/jba.v3i2.60
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown Policy Dilemma: COVID-19 Pandemic versus Economy and Mental Health

Abstract: Lockdown is considered to be the best of policies around the world to fight the deadly virus of COVID-19 which decimated hundreds of people in the last six months. However, this is not a cost-free measure. Billions of dollars worth of economic activities halted hinging upon these measures imposed by the governments of the countries. For instance, IMF predicted that the GDP growth will decline by 4.9 percent in 2020. Global trade is also expected to plummet by 27 percent in the second quarter of the year. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition, the Bangladesh government allowed the reopening of the markets and shopping centers on 10 May 2020, approximately three weeks ahead of 30 May 2022 (the official closure of the stay-at-home order nationwide) [56]. This could be why an increase in the crash, injury, and fatality statistics was recorded in six divisions (Khulna, Barishal, Rajshahi, Sylhet, Rangpur, and Mymensingh) out of the eight throughout the final three weeks of lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Bangladesh government allowed the reopening of the markets and shopping centers on 10 May 2020, approximately three weeks ahead of 30 May 2022 (the official closure of the stay-at-home order nationwide) [56]. This could be why an increase in the crash, injury, and fatality statistics was recorded in six divisions (Khulna, Barishal, Rajshahi, Sylhet, Rangpur, and Mymensingh) out of the eight throughout the final three weeks of lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 72% of respondents had insomnia, 61.7% were upset and angry at the pandemic situation and 83.5% expressed frustration and anxiety about the future. On an average 68.2% said they were overall terrified of the epidemic, and almost 59.4% said life becomes meaningless to them 10 . Another cross‐sectional web‐based survey among 1427 participants included in this survey.…”
Section: Methodsmentioning
confidence: 99%
“…9 A survey found that, during the COVID-19 pandemic, 72.6% of Bangladeshis suffer from insomnia. 10 Furthermore, the new reality of social isolation and other security measures puts everyone to the test, and people with mental illness may face even more difficulties this time. It is common for individuals to feel stressed and worried about a pandemic.…”
Section: Mental Health Condition In Bangladesh During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation